(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2022)
Helicobacter pylori is believed to be a main reason of stomach diseases in addition to the occurrence of infections that may end in cancer, there may be new virulence factors and as a result of the genetic analysis of this bacteria, which shows a wide view of the genome of this bacteria, so we hope to discover a new generation of genetic sequencers to verify the presence of new virulence agents. Studying the function of virulence factors possessed by H. pylori that increase its susceptibility to disease will lead to the possibility of developing treatments and vaccines. This review focuses on virulence factors and their role within pathogenesis of H. pylori contagion. This review contributes for development about new prevention and treatment methods based on an understanding of the role of cagA, vacA, ureE-H, and ureI proteins in increasing the susceptibility of bacteria to colonize the host digestive system in addition cause damage of host tissue.